The Effect of Professional Attitude on Motivation with a Strategic Management Perspective: The Mediating Role of Trust - Muhammed Ali Yetgin (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Employees' professional attitudes, motivation, and trust perceptions should be positive to be more successful and productive in their professions. Based on these research topics, the primary purpose of this study is to measure the effect of the trust mediation role and professional attitudes on the motivation of non-managerial employees working in the provincial units of a public institution in Ankara. The data obtained from 392 employees were analyzed using SPSS and AMOS programs, and structural equation modeling was used. As a result of the findings, it was understood that professional attitude did not have a statistically significant mediating effect on trust, and trust did not have a statistically significant mediating effect on motivation. According to the results obtained, professional attitude had a statistically significant impact on motivation. Increasing the perceptions of human capital, which is the most crucial resource of organizations, such as motivation and attitude towards work, will prevent negative situations such as leaving the organization and burnout syndrome.